Proinflammatory follicular helper T cells promote immunoglobulin G secretion, suppress regulatory B cell development, and correlate with worse clinical outcomes in gastric cancer. Issue 6 (May 2017) - Zhang, Hong; Yue, Rongxi; Zhao, Pengfei; Yu, Xuetao; Li, Junguo; Ma, Guoqing; Tang, Jiahong; Zhang, Lixin; Feng, Liying; Sun, Lidong; Song, Zongchang; Guo, Chunliang; et al.
Gastric cancer is one of the most common and aggressive malignancies. Both bacterial virulence factors and host chronic inflammation are thought to promote gastric cancer development. In this study, we investigated the potential involvement of follicular helper T cells in gastric cancer. Functions of follicular helper T subsets were examined in Helicobacter pylori –infected gastric cancer patients and H. pylori –infected but asymptomatic individuals. We found that the follicular helper T cells in gastric cancer individuals were skewed toward the Th1 and Th17 subsets compared to those in H. pylori –infected but asymptomatic individuals. In a naive B cell–follicular helper T cell coculture, the Th1–follicular helper T cells by themselves were ineffective at stimulating a robust antibody response, unlike the Th2–follicular helper T and Th17–follicular helper T cells. However, Th1–follicular helper T cells significantly promoted the immunoglobulin G response in collaboration with other follicular helper T subsets, through the secretion of interferon gamma. We also found that Th1–follicular helper T cells suppressed the development of interleukin-10 + regulatory B cells, a cell type previously thought to protect H. pylori –infected individuals from tissue damage. In addition, the frequency of Th1–follicular helper T cells in gastric cancer patients was negatively correlated with the disease-free survival of gastric cancer patients after tumor resection. These results suggested that dysregulation of follicular helper T subsets in gastric cancer patients, characterized by increased Th1–follicular helper T cells, contributed to inflammation and tumor development.